LEAD ISOTOPES IN NORTH PACIFIC DEEP WATER - IMPLICATIONS FOR PAST CHANGES IN INPUT SOURCES AND CIRCULATION PATTERNS - van de Flierdt T.; Frank M.; Halliday A.N.; Hein J.R.; Hattendorf B.; Günther D.; Kubik P.W. (My University, 2003)
The sources of non-anthropogenic Pb in seawater have been the subject of debate. Here we present Pb isotope time-series that indicate that the non-anthropogenic Pb budget of the northernmost Pacific Ocean has been governed by ocean circulation and riverine inputs, which in turn have ultimately been controlled by tectonic processes. Despite the fact that the investigated locations are situated within the Asian dust plume, and proximal to extensive arc volcanism, eolian contributions have had little impact. We have obtained the first high-resolution and high-precision Pb isotope time-series of North Pacific deep water from two ferromanganese crusts from the Gulf of Alaska in the NE Pacific Ocean, and from the Detroit Seamount in the NW Pacific Ocean. Both crusts were dated applying 10Be/9Be ratios and yield continuous time-series for the past 13.5 and 9.6 Myr, respectively. Lead isotopes show a monotonic evolution in 206Pb/204Pb from low values in the Miocene (≤18.57) to high values at present day (≥18.84) in both crusts, even though they are separated by more than 3000 km along the Aleutian Arc. The variation exceeds the amplitude found in Equatorial Pacific deep water records by about three-fold. There also is a striking similarity in 207Pb/204Pb and 208Pb/204Pb ratios of the two crusts, indicating the existence of a local circulation cell in the sub-polar North Pacific, where efficient lateral mixing has taken place but only limited exchange (in terms of Pb) with deep water from the Equatorial Pacific has occurred. Both crusts display well-defined trends with age in Pb–Pb isotope mixing plots, which require the involvement of at least four distinct Pb sources for North Pacific deep water. The Pb isotope time-series reveal that eolian supplies (volcanic ash and continent-derived loess) have only been of minor importance for the dissolved Pb budget of marginal sites in the deep North Pacific over the past 6 Myr. The two predominant sources have been young volcanic arcs, one located in the northeastern part and one located in the northwestern part of the Pacific margin, from where material has been eroded and delivered to the ocean, most likely via riverine pathways.